Introduction to the Special Issue on Ischemic Stroke in Children - Beata Sarecka-Hujar; Ilona Kopyta (MDPI AG, 2022)
The occurrence of arterial ischemic stroke (AIS) is a serious medical problem due to the deleterious neurological consequences that affect the daily functioning of the patient as well as the costs of medical care and rehabilitation [...]